Pengembangan Media Pembelajaran Berbasis Aplikasi Articulate Storyline 3 pada Pembelajaran Pendidikan Pancasila di Kelas V SD Wilayah I Lubuk Kilangan Kota Padang - Sitorus, Hiskia; Wulandari, Fikhen Tri; Anita, Yesi; Zuryanty, Zuryanty (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to develop a valid, practical, and effective Articulate Storyline 3 application-based learning media to be used in the learning process in elementary schools. The type of research used is Research and Development (R&D) with the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. The data collected includes the validity, practicality, and effectiveness of the media. The results of validation by experts showed a validity rate of 100% from subject matter experts, 97.7% from media experts, and 84.4% from linguists, with an average of 94.03% in the